2021
DOI: 10.17233/sosyoekonomi.2021.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Gender-Specific Life Expectancy in Turkey: A Time Series Analysis

Abstract: This paper analyses the socioeconomic determinants of Turkey's aggregate and genderspecific life expectancies from 1971 to 2017. The stationarity of data is checked with ADF, PP, and DFGLS unit root tests, while structural breaks are determined with the help of Zivot and Andrews (2002) unit root test. Also, ARDL bound test is conducted to identify co-integration. The estimated results show that the overall level of education, purchasing power, and economic development have a significant role in deciding the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Education has a significant effect on fertility rates, with higher levels of education often associated with lower fertility. This relationship has been extensively studied, as evidenced by research such as the work by Bleakley (2006) and Şentürk and Amjad (2021) analyzing exogenous changes in adult life expectancy and their impact on fertility.…”
Section: Effect Of Education On Fertilitymentioning
confidence: 99%
“…Education has a significant effect on fertility rates, with higher levels of education often associated with lower fertility. This relationship has been extensively studied, as evidenced by research such as the work by Bleakley (2006) and Şentürk and Amjad (2021) analyzing exogenous changes in adult life expectancy and their impact on fertility.…”
Section: Effect Of Education On Fertilitymentioning
confidence: 99%
“…In their study covering the period from 1971 to 2017 for Turkiye, Şentürk and Ali (2021) showed that educational factors, purchasing power, and economic development had a significant effect on life expectancy at birth for the Turkish population. They also indicated that population growth and negative environmental conditions were found to be insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that workers who had completed the training program had higher job satisfaction, better working conditions, and were more likely to receive promotions and salary increases (Bukhari and Zafar, Similarly, Ahmed et al ( 2016) conducted a study on the impact of scholarships on the education and well-being of female power loom workers in Okara. They found that the scholarships improved the educational outcomes and well-being of the female workers (Ahmed et al, 2016;Şentürk & Ali, 2021). Access to healthcare facilities is one of the most significant health incentives for employees in the power loom industry.…”
Section: Social Justice and Workplacementioning
confidence: 99%
“…), the power loom sector in Pakistan is responsible for the employment of more than 3.5 million people, the majority of whom come from families with lower incomes. These workers are provided with a means of subsistence by the industry, which also contributes to an improvement in their level of living (Abuhashesh, et al, 2019;Şentürk & Ali, 2021). To summarize, the power loom business in Pakistan is of great importance to the country's economy, employment market, international trade, and traditional handicrafts market.…”
Section: Introductionmentioning
confidence: 99%